The role of digital reading corner in increasing the community's reading interest in Bekasi district - Dewanti, Nur; Riady, Yasir (Mitra Palupi, 2024)
Background: A culture of interest in reading or literacy movement must be fostered in Indonesian society. Purpose: The aim is to describe the existence of a Digital Reading Corner (POCADI) managed by the Bekasi Regency Archives and Library Service, which shows an increase in people's interest in reading in the Bekasi Regency. Design and methods: This article uses qualitative research and a literature review. Data collection techniques in the field are observation and interviews. The research objects in the field are visitors and officers at the Digital Reading Corner location. Collections of digital media such as computers, Android tablets, e-books, LED TV, and Wi-Fi increase visitors' enthusiasm to increase their interest in reading. The efforts of the Bekasi Regency Archives and Library Service in managing POCADI include outreach to the community, educational visits from schools to POCADI and storytelling activities. Results: The results of the research can be concluded that the Digital Reading Corner provides benefits in increasing people's interest in reading in the Bekasi district, namely as a place to read with a collection of reading materials equipped with digital media, a place to read for people who are located far from the Bekasi Regency Public Library